2005
DOI: 10.1002/cne.20521
|View full text |Cite
|
Sign up to set email alerts
|

Medial vestibular connections with the hypocretin (orexin) system

Abstract: The mammalian medial vestibular nucleus (MVe) receives input from all vestibular endorgans and provides extensive projections to the central nervous system. Recent studies have demonstrated projections from the MVe to the circadian rhythm system. In addition, there are known projections from the MVe to regions considered to be involved in sleep and arousal. In this study, afferent and efferent subcortical connectivity of the medial vestibular nucleus of the golden hamster (Mesocricetus auratus) was evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 144 publications
4
68
1
Order By: Relevance
“…Some studies found prolonged quiet sleep during vestibular stimulation (Barnard and Bee, 1983;Johnston et al, 1997;Korner et al, 1990), while other studies found that it promoted wakefulness (Campos, 1994;Gregg et al, 1976), which is also in line with literature suggesting an influence of vestibular cues on arousal and sleep regulation (e.g. Horowitz et al, 2005). The velocity of rocking has been suggested to be crucial (Johnston et al, 1997): slower speed is thought to promote sleep (Gregg et al, 1976) while faster speed or a fall is thought to promote wake states (Campos, 1994) or even wake an organism from sleep (Horner et al, 1997).…”
Section: Vestibular Stimulation For General Soothing Effects and Imprsupporting
confidence: 78%
See 2 more Smart Citations
“…Some studies found prolonged quiet sleep during vestibular stimulation (Barnard and Bee, 1983;Johnston et al, 1997;Korner et al, 1990), while other studies found that it promoted wakefulness (Campos, 1994;Gregg et al, 1976), which is also in line with literature suggesting an influence of vestibular cues on arousal and sleep regulation (e.g. Horowitz et al, 2005). The velocity of rocking has been suggested to be crucial (Johnston et al, 1997): slower speed is thought to promote sleep (Gregg et al, 1976) while faster speed or a fall is thought to promote wake states (Campos, 1994) or even wake an organism from sleep (Horner et al, 1997).…”
Section: Vestibular Stimulation For General Soothing Effects and Imprsupporting
confidence: 78%
“…The velocity of rocking has been suggested to be crucial (Johnston et al, 1997): slower speed is thought to promote sleep (Gregg et al, 1976) while faster speed or a fall is thought to promote wake states (Campos, 1994) or even wake an organism from sleep (Horner et al, 1997). On a neurophysiological level, an animal model showed that the medial vestibular nucleus projects onto hypocretin neurons and thus regulates sleep and arousal (Horowitz et al, 2005).…”
Section: Vestibular Stimulation For General Soothing Effects and Imprmentioning
confidence: 99%
See 1 more Smart Citation
“…For example GVS increases GABA release in rats (Samoudi et al, 2012). But also the sleep-wake system is influenced by vestibular input as projections of the medial vestibular nucleus to hypocretin neurons and vice versa have been found (Horowitz et al, 2005).…”
Section: What Neurophysiological Mechanisms Can Explain the Effect Ofmentioning
confidence: 99%
“…Given the positive effect of arousal on memory retention (e.g. Sharot and Phelps, 2004), one could speculate that such results might be explained by arousal caused by vestibular stimulation (Horowitz et al, 2005, see also chapter 2.1). To further investigate this interesting question on the influence of vestibular-induced arousal, one could use different strengths of vestibular stimulation to see whether the positive effect on memory depends on stimulation parameters.…”
Section: Cognitive Enhancement Through Vestibular Stimulation?mentioning
confidence: 99%